The Role of Islamic Religious Education Teachers and Parents in Discipline Students's Worship in Madrasah Tsanawiyah - Yusri Purnama Anju Nasution; Amiruddin Siahaan; Zulheddi Zulheddi (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study is to determine the form of cooperation, application, and obstacles for PAI teachers and parents in disciplining student worship. This research uses qualitative research, with a phenomenological approach. The subjects of this study were 6 the Principal, Vice Principal, PAI Teacher in the Field of Akidah Akhlak Study and the field of Jurisprudence, and 2 guardians of class VII and VIII students. This study used primary data and secondary data as data sources. Meanwhile, data collection tools through interviews/interviews, observations, and documentation. The data analysis techniques used are data reduction, data presentation, and puff withdrawal. To promote the validity of the data, it is carried out by extending the period of observation, triangulation, careful observation, and holding members and checks so that the information obtained can be used in research following what the informant means. Based on the findings, the results were obtained that the form of cooperation carried out by teachers with parents was through the madrasa committee and also tools in the form of mutaba'ah books, liaison books, and social media group accounts. The way to implement cooperation between PAI teachers and parents is to provide a good example or example, then provide advice and control every student activity. The obstacles faced by teachers and parents of students are parents not attending meetings held by teachers at school, students often forgetting to bring mutaba'ah books, and parents often forgetting to fill in mutaba'ah books so that children often fill in their mutaba'ah books. Based on this, the solution that is carried out to facilitate cooperation between teachers and parents is using continuous communication and frequent meetings to support the success of an activity that has been systematically compiled and planned.